2013
DOI: 10.1007/s00221-013-3545-x
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying connectivity via efferent and afferent pathways in motor control using coherence measures and joint position perturbations

Abstract: The applicability of corticomuscular coherence (CMC) as a connectivity measure is limited since only 40-50 % of the healthy population presents significant CMC. In this study, we applied continuous joint position perturbations to obtain a more reliable measure of connectivity in motor control. We evaluated the coherence between joint position perturbations and EEG (position-cortical coherence, PCC) and CMC. Healthy subjects performed two isotonic force tasks against the handle of a wrist manipulator. The basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 58 publications
2
33
0
Order By: Relevance
“…5 to 8 for an example subject (Subject 10, number of data segments: 942). In line with a previous study [36], the linear interaction (the first order harmonic coupling) was shown between the perturbation and EEG. High order (≥ 2) harmonic and intermodulation couplings were detected for this subject, as well as subharmonic coupling for 29 Hz (1:2).…”
Section: B Application To the Human Proprioceptive Systemsupporting
confidence: 92%
See 2 more Smart Citations
“…5 to 8 for an example subject (Subject 10, number of data segments: 942). In line with a previous study [36], the linear interaction (the first order harmonic coupling) was shown between the perturbation and EEG. High order (≥ 2) harmonic and intermodulation couplings were detected for this subject, as well as subharmonic coupling for 29 Hz (1:2).…”
Section: B Application To the Human Proprioceptive Systemsupporting
confidence: 92%
“…visual flickering) has often been reported in the human visual system [3,7]. Most studies using somatosensory stimuli, mainly using tactile stimuli,) only reported harmonic and intermodulation coupling (see [8,10,14,36,41] for examples and a brief review is available in [42]). To the best of our knowledge, only Langdon and his colleagues has reported 2:3 subharmonic coupling between brain responses and tactile vibrations [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanical (i.e. joint angle and torque) and EMG recordings obtained from continuous mechanical TNSRE-2015-00235 stimulation also show a small response at non-stimulated frequencies [18][19][20]. Nonlinear responses in the sensorimotor system could result from sensors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…When studying sensory and motor function after stroke with CMC, no information can be obtained from individuals without voluntary muscle control. Finally, a large downside for the potential clinical application of CMC is that it cannot be detected in all cases: even healthy subjects, with normal voluntary motor control, do not all present CMC (Ushiyama et al, 2011;Mendez-Balbuena et al, 2011;Campfens et al, 2013). The inter-individual difference in the presence of CMC reflect physiological inter-individual differences in the strength of the oscillatory corticomuscular coupling and are not the result of technical aspects such as the (mis-) placement of EEG electrodes (Ushiyama et al, 2011).…”
Section: Introductionmentioning
confidence: 99%